RANCANG BANGUN APLIKASI PENGADUAN MASYARAKAT BERBASIS MOBILE DI LINGKUNGAN PERKUTUT HELVETIA TENGAH - Nababan, Maria Tesalonika; Siringoringo, Rimbun; Harianja, Eva Julia G. (Universitas Methodist Indonesia, 2023)
The rapid development of information technology encourages the opening of opportunities for all aspects of life, including the public sector of the state apparatus which is held at the sub-district or sub-district level. Efforts to improve public services are a form of bureaucracy designed to encourage community participation and create good governance. The Perkutut II environmental community complaint application is an application designed to assist the community in submitting complaints that occur in the surrounding environment. The expected result is to increase community participation, a good complaint application will encourage active community participation in reporting problems and issues that affect them. With an easy-to-use platform and good accessibility, people will feel more involved and play a role in building a good community.